Language practice, language management and language ideology in Malaysian schools / Soon Chiow Thai @ Soon Yit Fang - Soon , Chiow Thai @ Yit Fang (2019)
This thesis focuses on the use of language (practice), the belief in language (ideology) and how language is maintained (management). It uses Spolsky’s (2009) Theory of language management which looks at how language policy affects language practice and language belief among users. In particular, this thesis looks into details how the three languages of English, Malay and Mandarin are used in the context of Malaysian secondary schools. Through this study, the relationship between language practice and language ideology is revealed. In addition, it also sheds light on the impact of language management on language practice and language ideology. Three types of Malaysian schools were identified as the research sites: one Chinese Independent high school (Mandarin as the medium of instruction), two national type secondary schools (Malay as medium of instruction but Mandarin is also predominant) and eleven (11) national secondary schools (Malay as medium of instruction); English and Malay are both compulsory subjects to be taught in all the three types of school. The aim is to gather an understanding on how the three languages of English, Malay and Mandarin are used. A total of 422 students and 376 teachers served as participants. Two approaches were applied for data collection: questionnaires and interviews. SPSS version 22 was used to analyse the primary data while the 15 interviews were analysed based on contents related to the interview questions. The findings of this thesis indicate a number of outcomes: a) the frequency in using (practice) Mandarin and Malay among students and teachers in the Chinese Independent high school students and teachers is contrary to the practice of students and teachers in national type secondary schools and national secondary school; b) the students and teachers have ‘neither agree nor disagree’ language belief (ideology) towards Malay and Mandarin; c) although students and teachers among the three schools have a high belief (ideology) in English, it was hardly used (practice) in the classroom where Mandarin and Malay are used as the medium of instruction of the schools; d) the language practice of students are very weakly correlated their language ideology in three languages, English, Malay and Mandarin. e) the language policy implemented in Malaysian secondary schools has a positive impact on the language practice and language ideology of students only (not the teachers). From the outcome of this thesis, it is hereby recommended that Malaysia’s education policy makers, in particular those working on language policies, pay attention to the gap currently existing between the language ideology and language practice among students and teachers, when designing and attempting to promulgate new language policies. This is because the outcome of this thesis clearly shows that teachers may have more influence over their students. In this regard, the current thesis indicates that it was the teachers’ language practice that had determined the language practice of the students.